The Information Content of Dividend Surprises: Evidence from Germany. (22nd July 2013) - Andres, Christian; Betzer, Andre′; van den Bongard, Inga; Haesner, Christian; Theissen, Erik
Abstract: This paper reconsiders the issue of share price reactions to dividend announcements. We use the difference between the actual dividend and the analyst consensus forecast as obtained from I/B/E/S as a proxy for the surprise in the dividend announcement. Using data from Germany, we find significant share price reactions after dividend announcements. We use panel methods to analyze the determinants of the share price reactions and find evidence in favour of the cash flow signaling hypothesis and dividend clientele effects. We further find that the price reaction to dividend surprises is related to the ownership structure of the firm. The results do not support the free cash flow hypothesis. An additional result of our analysis is that dividend changes are not an appropriate measure to capture the information content of dividend announcements.